Stratigraphy and Mineralogy of Balambo Formation (Aptian - Cenomanian) near Chomabrok village, Imbrication Zone, Iraqi Kurdistan Region - Aheen O. Abdullah; Sardar M. Balaky (Tikrit Journal of Pure Science)
The stratigraphy and mineralogy of Balambo Formation (Aptian - Cenomanian) in exposed surface section near Chomabrok village in the Imbrication zone, northeastern Iraq is studied. The Formation is 450 meters thick and consists of thin to medium to thick bedded yellowish-brown, and black to dark gray limestones, marly limestones, with thin- medium bedded, grayish - black marl and shale, with thin bands of black cherts and abundant nodules and lenses. From the field observations and petrographic studies, the formation mainly made from two main lithofacies types; marly limestone-marl lithofacies and cherty limestone lithofacies. The petrographic study of carbonate rocks deepened on 79 thin sections and demonstrated that the carbonates of Balambo Formation composed of micrite ground mass with abundant skeletal grains; planktonic and some benthic foraminifera, radiolaria, calcisphere, ostracods, pelecypods, larva-ammonoids, small-brachiopods, sponge spicules, echinoid spines, and bioclasts. Non-skeletal grains include peloids only. Using extraction method and according to an assessment of foraminiferal assemblages and based on the defined planktonic foraminifera the assigned age of Balambo Formation in the studied section is Aptian to Cenomanian as upper Balambo age. The results of X-ray diffraction (XRD) analysis for bulk mineralogy of selected shale and marl samples suggested the presence of phyllosilicate with abundant calcite, common quartz, and moderate Fluorapatite with minor dolomite content. Illite is the dominant clay mineral in the Balambo Formation and indicates a hot, arid climate during most of the Cretaceous period in the Imbrication zone, Northeastern Iraq.